Enhancement of an Effective Training in Manufacturing Company - Wan Mahmood, Wan Hasrulnizzam; Mohamad, Effendi; Abdullah, Abd Rahman (2008)

(untitled)
The purpose of this paper is to disclose of how trainings were conducted in a manufacturing company towards an effective training. A company was selected for case study. The company is one of the leading companies in composite technology which situated in Melaka, Malaysia and currently active in educating staff towards implementation of Lean Manufacturing system. This paper is only focused on the training of Value Stream Mapping (VSM) which considered the new method for Lean manufacturing system in the company. This paper will disclose the activities which applied during class and the success story in order to have 100 percent participation and training effectiveness after class. In addition, it’s expected to guide the trainer to make preparation before, during and after class in industrial practice.